The English Debating Self-Efficacy Scale: Scale development, validation, and psychometric properties - Fanghua Liu; Yanchao Yang; Feng (Robin) Wang; Wangze Li (PLoS ONE, 2025)
The importance of English debate in fostering critical thinking and the role of self-efficacy in enhancing confidence and performance in this domain are widely acknowledged. However, a significant gap exists in the literature regarding the measurement of self-efficacy specifically within English debate. This research seeks to fill this gap by developing and validating an English Debate Self-Efficacy Scale (EDSS). Using a sample of 1,259 participants from an independent college in Hebei Province, China, the study divided participants into two groups: 613 for exploratory factor analysis (EFA) and 646 for confirmatory factor analysis (CFA), with convenience sampling as the chosen methodology. EFA revealed three core dimensions of debate-related self-efficacy: Language proficiency (Cronbach’s Alpha = .894), Debating skills (Cronbach’s Alpha = .861), and Team collaboration (Cronbach’s Alpha = .831). Subsequent CFA validation with an independent sample confirmed the scale’s structure, demonstrating strong structural, convergent, and discriminant validity. Additionally, significant correlations between the English Debate Self-Efficacy Scale and the English Proficiency Self-Efficacy Scale supported the scale’s criterion validity. These findings underscore the scale’s potential as a reliable tool for assessing self-efficacy in English debate contexts, offering valuable insights for research, teaching, and training in educational settings. Limitations related to sample representativeness and research design were also discussed, providing a foundation for future studies to expand upon. In conclusion, the English Debate Self-Efficacy Scale (EDSS) is a reliable and valid instrument for measuring self-efficacy in the context of English debate.